Simulation of the electron beam in a TEM as a charged particles flux - Hernández-Valle, Alberto (2015)
The behavior of an electron beam in a TEM was simulated as a function of accelerating voltage, excitation current of the lenses and relative permeability of the pole pieces, by the software COMSOL Multiphysics version 4.2a. The results showed a low vertical speed of stray electrons, which were filtered by the diaphragms. Moreover, the plots displayed an increase in the magnetic flux density with the increase of the magnetic permeability of the pole pieces. Furthermore, the outcome indicated that a boost in the magnetic flux density increased the angle of divergent electrons and reduced their vertical speed. Finally, the observations illustrated that the number of electrons at the inlet does not affect the beam overall behavior nor the magnetic flux density magnitude.